Novel mutations in the SPAST gene cause hereditary spastic paraplegia. (December 2019) - Zhu, Zeyu; Zhang, Chao; Zhao, Guohua; Liu, Qing; Zhong, Ping; Zhang, Mei; Tang, Weiguo; Zhan, Feixia; Tian, Wotu; Wang, Yan; Yin, Kaili; Huang, Xiaojun; et al.
Abstract: Background: Mutations in the SPAST gene are the most frequent cause of hereditary spastic paraplegia (HSP). We aim to extend the mutation spectrum of spastic paraplegia 4 (SPG4) and carried out experiment in vitro to explore the influence of the SPAST gene mutation on the function of corresponding protein. Methods: Whole-exome sequencing (WES) combined with multiplex ligation-dependent probe amplification (MLPA) were performed in a cohort of 150 patients clinically diagnosed with HSP. We focus on screening for mutations in SPAST gene and carrying out functional experiments to assess the effects of the novel variants. Results: A total of 34 different mutations in the SPAST gene were identified, of which 10 were novel, including 1 missense (c.1479T > A), 1 nonsense (c.766G > T), 3 splicing (c.1413 + 1_1413+4delGTAA, c.1729-1G > A and c.1536+2T > G) and 5 frameshift mutations (c.1094delC, c.885dupA, c.517_518delAG, c.280delG and c.908dupC). For 7 novel non-splicing mutations, functional study showed that accumulated M1 spastin colcocalized with microtubules which was different from a uniformly diffused M87 spastin. While an impairment in severing activity was observed in both mutant M1 and mutant M87, except for c.280delG. All 3 novel splicing variants w ere predicted to affect splicing by using bioinformatic programs. However, only c.1536+2T > G had no influence on splice site in vitro, which conflicts with the in-silico analysis. Conclusion: We genetically diagnosed 40 SPG4 patients. All the novel non-splicing mutations except for c.280delG were certified to exert an effect on the microtubule-severing and all the novel splicing mutations other than c.1536+2T > G would cause abnormal splicing of the spastin. Highlights: A total of 34 different mutations in the SPAST gene were identified, of which 10 were novel. Functional studies were carried out to assess the effects of novel variants identified in our corhort. We extend the mutation spectrum of spastic paraplegia 4 (SPG4) and summarize the clinical characters of 40 SPG4 patients.